Influência dos padrões arquiteturais de teias orbiculares sobre a eficiência de de interceptação e retenção de presas - Xavier, Gabriel Máximo (2020)
We investigated two great issues on orb-web spiders’ ecology: the prey capture and the building behaviour. As the webs mediate these issues, we also dedicate a chapter (Chapter 1) to improve the capture threads length’ estimators since this variable is important to this research field. Thus, by means of a simplified mathematical reasoning, we proposed two new formulae. These formulae produced accurate estimates and, then, can be used in this type of investigation. When we assessed (Chapter 2) the influence of distinct spider behaviours and many orb-web architectural traits over the prey capture, we verified the web capture area and period of the interactions exert predictive power over the captures of insects of different sizes. Then, these variables were discussed as functional features determining the interactions between spiders and prey. Finally, we investigated (Chapter 3) the predictive power of traditional hypotheses to behavioural decisions in orb web building. Thus, we conducted an assessment in order to find a simplified and generalizable explanation to these behaviours in such way to correct analytical problems from previous studies. Ultimately, we found that, despite plausible, some of the traditional explanations have limited application. The need to compensate the greater spent time to achieve the intercepted prey, in its turn, proves to be important enough to widely which is the optimal manner to distribute the sticky threads along the web.